Managing tourist expectations in nature-based tourism: Strategies for enhanced perception - Kumar, Paramjeet; Kulshreshtha, Sharad Kumar; Kumar, Rajesh (Journal of Tourism Management Research, 2025)
Nature-based tourism is gaining popularity as people seek meaningful experiences that combine adventure, leisure, and personal growth. This study explores how novelty, self-improvement, nature connection, knowledge, fitness, and escape influence tourists’ perceptions in ecotourism. This study offers a thorough framework for comprehending tourist pleasure and engagement by combining several definitions of nature-based tourism and examining these motivating factors. SEM was used to analyze the relationship among the factors and the indicators. The results indicate that all four motivating elements have a major influence on travelers’ overall opinions, highlighting their need for unusual experiences, closer linkages to the natural world, opportunities for personal growth, and a break from everyday life. These observations emphasize how crucial it is to provide tourist experiences that satisfy the psychological and emotional requirements of visitors. Offerings that are in line with the reasons behind travel can improve tourist experiences, encourage brand loyalty, and guarantee sustainable tourism growth, all of which are advantageous to industry stakeholders and long-term viability. This study has important ramifications for legislators, tourism planners, and destination marketers, recommending that ecotourism destinations modify their offerings to improve tourist pleasure and encourage environmentally friendly travel methods.